A review of developments in technologies and research that have had a direct measurable impact on sustainability considering the Paris agreement on climate change. (February 2017) - Foley, Aoife; Smyth, Beatrice M.; Pukšec, Tomislav; Markovska, Natasa; Duić, Neven
Abstract: This special issue of Renewable and Sustainable Energy Reviews is devoted to the research presented and discussed at the 10th Conference on Sustainable Development of Energy, Water and Environment Systems (SDEWES) held from the 27th September to the 2nd October 2, 2015 in Dubrovnik, Croatia. The contents are in in keeping with the aims and scope of the journal which is to bring together under one roof the current advances in the ever broadening field of renewable and sustainable energy. The articles published in this special issue review, discuss and examine energy resources and technologies (e.g. biomass, hydropower, solar, geothermal and wind), applications and services (e.g. buildings, industry, electricity and transport) and policy and the environment (e.g. economic, emissions, politics, energy planning, social aspects) within the framework of sustainable development. A total of 35 extended manuscripts were invited by the guest editors of this special to submit candidate articles for consideration for publication in Renewable and Sustainable Energy Reviews. After a vigorous review process by expert reviewers overseen by the guest editors a total of 22 articles were accepted for publication.